The Effect of Chromium Exposure on Creatinine and Bun Level of Tanners in Leather Industry in Magetan (Indian Journal of Forensic Medicine & Toxicology, 2020)
Chromium in the leather tanning industry can have an impact on workers’ health. Kidney disease is often referredto as a side effect from exposure to chromium. Measurement of creatinine and BUN level is a method of examiningkidney function.The purpose of this study was to analyze the effect of chromium exposure on creatinine and BUN level in leathertanning workers in small leather industry in Magetan. This type of research is observational with cross sectionaldesign. The sample of the study was 13 exposed worker groups namely chromium operators and 13 unexposedgroups namely administrative workers.The results showed that there were differences in the average levels of urine chromium in chromium operatorsand administrative workers (p-value = 0,000), there were differences in the average creatinine levels in chromiumoperators and administrative workers (p-value = 0,031), and there were no difference in the average level of BUNin chromium operators and administrative workers (p-value = 0,644). There were no influence of chromium levelsin urine on the increase in creatinine levels (p-value = 0,189) and BUN (p-value = 0,854) in tanning workers, with asignificance value of p-value> 0,05.The conclusion of this study had that chromium was no effect on creatinine and BUN levels. High levelsof urine chromium in tanning workers indicate a health risk that requires control effort. Suggestion given isthat the tanners need periodic health examination, keep personal hygiene before and after working as wellas using Personal Protective Equipment (PPE).
Keywords: chromium, creatinin, BUN, leather tanning